2013
DOI: 10.1111/inr.12017
|View full text |Cite
|
Sign up to set email alerts
|

Newborn care in Nepal: the effects of an educational intervention on nurses' knowledge and practice

Abstract: This was the first study of its kind in Nepal, a small step in enhancing nurses' abilities to improve their knowledge and competence regarding care of newborns. However, continued education and guidance are required to sustain knowledge and competence in practice, and our educational intervention needs further testing with other populations of nurses. There are various policy implications required to enable this to happen. This includes health ministry funding and support for in-service education; hospitals an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…The efficacy of this approach has been confirmed by other studies of neonatal nursing knowledge pertaining specifically to infant nursing care (Shrestha et al. ; Tiryaki & Cinar ; Chen et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficacy of this approach has been confirmed by other studies of neonatal nursing knowledge pertaining specifically to infant nursing care (Shrestha et al. ; Tiryaki & Cinar ; Chen et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Shrestha et al. () suggest that periodic training and educational programs for neonatal nurses would enhance their knowledge. Advancing nursing knowledge and developing caring skills through continuous education would serve to enhance their professional values (Brown et al.…”
Section: Introductionmentioning
confidence: 99%
“…Five (50.0%) of these studies showed significant performance falloff over the time period analyzed. 37,38,48,56,66 Three studies (30.0%) showed no falloff 41,43,52 ; the 2 remaining studies (20.0%), both from Ethiopia, found varying levels of retention in different groups of birth attendants, with higher levels of training associated with less falloff. 55,67 These latter 5 studies showing either no falloff or mixed results included the 4 longest running studies in our literature review, ranging from 9 months to 2 years.…”
Section: Retention Of Knowledge and Skillsmentioning
confidence: 99%
“…43 Furthermore, in the self-directed study group, training costs were significantly lower. Self-directed study was analyzed in 1 other article, in which Shrestha et al 66 reported significant acquisition of knowledge and skills by Nepali nurses who underwent a self-directed educational intervention. Both knowledge and skills declined over subsequent months after the training but remained above pretraining levels when the study ended 3 months after the intervention.…”
Section: Controlled Trials Of Training Strategiesmentioning
confidence: 99%
“…Nurses who are more caring employ more patient-centered caring skills in clinical practice, and patients feel more cared for and satisfied with the nursing care [18]. Educational programs enhance nurses' caring knowledge and practical competence to ensure that patients are willing to receive treatment, thereby enhancing patient satisfaction [16] [19]. The results of this study revealed that the scores of nurse caring and patient satisfaction significantly increased between the pretest and the posttest.…”
Section: Discussionmentioning
confidence: 83%